Perinatal Anesthesia Exposure and Autism Spectrum Disorders. Issue 1 (6th January 2023) - Houck, Philipp; Naus, Claire; Croen, Lisa; Sun, Lena S.
Abstract : Epidural analgesia is frequently used during labor among pregnant people in the United States. Different factors have been associated with the development of autism spectrum disorder in the epidemiological literature: maternal health, infectious and pharmacological etiologies, social factors, and environmental exposures. Current data indicates no clear association between the use of epidural labor analgesia and the development of autism spectrum disorder in the offspring. This review presents the public health perspective on the postulated association between perinatal anesthesia exposure and autism spectrum disorders.